Escola técnicas agrícolas: um estudo sobre ensino de Matemática e formação de professores - Salandim-Martins, Maria Ednéia [UNESP]; Garnica, Antonio Vicente Marafioti [UNESP] (My University, 2010)
The central focus of this paper is to establish that the Brazilian Education Programa to prepare professionals in Technical-Agricultural Schools is suffering a kind of marginalization which comes from two distinct perspectives: the intention to prepare professionals (being a branch of Technical Education) and the relationship to the countryside (a community space historically seen as peripheral in its relation to urban culture). The paper discusses – from a historical and sociological point of view and using Oral History as methodological approach – the experiences of Math’s teachers in their daily struggles against some conceptions of other teachers (mainly those of technical areas) and against all the “regular” schooling system.

Valendo-se da metodologia da História Oral, este artigo pretende estudar a formação de professores de Matemática e suas práticas relativas ao ensino de Matemática em Escolas Técnicas Agrícolas. Com base em uma síntese histórico-sociológica sobre o panorama rural brasileiro, a constituição do ensino técnico e o desenvolvimento do ensino técnico agrícola, este artigo defende que as escolas técnicas agrícolas sofrem uma dupla marginalização: por um lado, proveniente de sua natureza profissionalizante, e, por outro, dada sua vinculação com o meio campesino. Tal marginalização ocupa também o interior das escolas, onde os professores de Matemática executam uma coreografia de resistências e acomodações em relação aos professores das áreas técnicas e, de modo geral, ao sistema regular de ensino.
Technical Education related to Agricultural affairs: some remarks on teachers preparation and mathematics education
Keywords: Technical-Agricultural schooling system; History of Brazilian mathematics education; Teachers formation; Math’s teaching and learning; Escolas Técnicas Agrícolas; História da educação matemática brasileira; Formação de professores; Ensino de Matemática